2022
DOI: 10.3390/cancers14174192
|View full text |Cite
|
Sign up to set email alerts
|

Paving the Way to Solid Tumors: Challenges and Strategies for Adoptively Transferred Transgenic T Cells in the Tumor Microenvironment

Abstract: T cells are important players in the antitumor immune response. Over the past few years, the adoptive transfer of genetically modified, autologous T cells—specifically redirected toward the tumor by expressing either a T cell receptor (TCR) or a chimeric antigen receptor (CAR)—has been adopted for use in the clinic. At the moment, the therapeutic application of CD19- and, increasingly, BCMA-targeting-engineered CAR-T cells have been approved and have yielded partly impressive results in hematologic malignancie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 283 publications
0
4
0
Order By: Relevance
“…A phase I clinical study showed that docetaxel can increase CTL in colorectal cancer patients while simultaneously reducing CD25+CD4+ T cells, thereby enhancing the body’s antiviral response. On the other hand, vincristine can inhibit the proliferation of IL-10 secreting Tregs ex vivo, while upregulating antigen-specific CTL ( 75 , 76 ). Thalidomide and its derivatives can be used to treat multiple myeloma ( 77 ).…”
Section: Addressing Treg Proliferation and Inflammatory Reprogramming...mentioning
confidence: 99%
“…A phase I clinical study showed that docetaxel can increase CTL in colorectal cancer patients while simultaneously reducing CD25+CD4+ T cells, thereby enhancing the body’s antiviral response. On the other hand, vincristine can inhibit the proliferation of IL-10 secreting Tregs ex vivo, while upregulating antigen-specific CTL ( 75 , 76 ). Thalidomide and its derivatives can be used to treat multiple myeloma ( 77 ).…”
Section: Addressing Treg Proliferation and Inflammatory Reprogramming...mentioning
confidence: 99%
“… 25 , 26 However, the tumor microenvironment (TME) can limit T cell antitumor efficacy by impacting various fitness traits, including survival, proliferation, and functional persistence. 27 , 28 , 29 This can be driven by distinct stimulation contexts, resulting in cell differentiation into several states. For example, different intensity and duration of stimulation determine whether, and to what extent, T cells can exert their effector functions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, when CARs are added to T-cells, they can be designed to specifically recognize and bind to these proteins or gangliosides on the surface of cancer cells (8). This recognition triggers the activation of the T-cells and leads to the destruction of the cancer cells; to date, four generations of CARs have been created (9). The first-generation CARs only possess an intracellular signaling domain of CD3ξ to activate T cells (10).…”
Section: Introductionmentioning
confidence: 99%